Cues for coaching athletes during the COVID-19 second wave - Teodorescu, S.; Dutheil, F.; Urzeala, C. (Isokinetics and Exercise Science, 2021)
Given the alarming number of cases reported daily [1] sportsmen need to be prepared for a second wave of COVID-19. The first lockdown definitely found athletes, coaches and the entire staff unprepared. The extension of bans on training under normal conditions, the suspension of competitions and the uncertainty regarding the time of resuming training activities had a negative impact on sports. The involved actors hardly handled online workouts, athletes did their best to practice in narrow spaces or outdoors, coaches struggled with technology, and managers asked for reports. To fight future similar effects, in case of the COVID-19 second wave, we propose several dimensions of the lockdown preparation, starting from a coaching model with four components: Problem identification - the overall goal will be to maintain each athlete`s general and specific physical fitness Action - planning and implementing lockdown training Assessment Feedback The COVID-19 second wave should firstly mean responsibility and motivation, but also entertainment and cognitive arousal. Athletes need to feel that they are more than lottery winners at the Olympics for coaches and managers.